2019
DOI: 10.1016/j.resuscitation.2019.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Passive leg raising in out-of-hospital cardiac arrest

Abstract: Background: The chances of survival after an out-of-hospital cardiac arrest (OHCA) are one in ten. The majority of survivors have no or relatively mild neurological sequelae. Interventions are time critical and well-timed management is challenging. All aspects of resuscitation in an OHCA are based on knowledge of clinically important actions and their timing in OHCA management. Randomised trials face ethical and legal barriers. The victim is unable to give informed consent and obtaining consent from a legal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 140 publications
1
17
0
Order By: Relevance
“…The survival results in our study are in the same line as those obtained by an observational study that introduced PLR in the treatment of OHCA and compared its effectiveness with a matched group that received standard treatment. In this Swedish study, PLR was performed more often in cases with a worse clinical scenario and it was suggested that early leg elevation could improve its benefit on survival [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survival results in our study are in the same line as those obtained by an observational study that introduced PLR in the treatment of OHCA and compared its effectiveness with a matched group that received standard treatment. In this Swedish study, PLR was performed more often in cases with a worse clinical scenario and it was suggested that early leg elevation could improve its benefit on survival [15].…”
Section: Discussionmentioning
confidence: 99%
“…A study of OHCA showed that 20º of leg elevation helped to increase cardiac output during CPR [14]. Despite these promising hemodynamic results, a recent observational study introducing PLR into the standard treatment of patients with OHCA found no difference in survival compared to a control group [15].…”
Section: Introductionmentioning
confidence: 99%
“…The survival results in our study are in the same line as those obtained by an observational study that introduced PLR in the treatment of OHCA and compared its effectiveness with a matched group that received standard treatment. In this Swedish study, PLR was performed more often in cases with a worse clinical scenario and it was suggested that early leg elevation could improve its bene t on survival (11).…”
Section: Discussionmentioning
confidence: 99%
“…A study of OHCA showed that 20º of leg elevation helped to increase End Tidal CO2 (ETCO2) during CPR (10). Despite these promising hemodynamic results, a recent observational study introducing PLR into the standard treatment of patients with OHCA found no difference in survival compared to a control group (11).…”
Section: Introductionmentioning
confidence: 99%
“…A Swedish research group reported that PLR was performed more often in cases involving a worsened clinical scenario and early PLR could improve its benefit on survival. (9) The idea of a transient effect of PLR over time has been described among patients with septic shock and is attributed to capillary leak. (10) During acute circulatory failure, maintained tissue perfusion which could favor the shortened effect of PLR on CO. (11) Optimizing venous return is the key to improve survival outcomes.…”
Section: Discussionmentioning
confidence: 99%